Effect of Repeated Earthquake on Inelastic Moment Resisting Concrete Frame - Ade Faisal, Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This paper investigates the response of inelastic moment resisting concrete building under repeated earthquakes. 2D models consist of 3-storey, 6-storey and 9-storey representing low to medium rise building frame were designed using seismic load and ductility class medium (DCM) according to the requirements set by Euro Code 8. Behaviour factor and stiffness degradation were also taken into consideration. Seven sets of real repeated earthquakes as opposed to artificial earthquakes data were used. The response of the frame was measured in terms of the inter-storey drift and maximum displacement. By adopting repeated earthquake, the recorded mean IDR increased in the range of 3% - 21%. Similarly, in the case of maximum displacement, the values also increased from 20 mm to 40 mm. The findings concluded that the effect of using repeated earthquake in seismic analysis considerably influenced the inter-storey drift and the maximum displacement.